Telaah Kembali Pemahaman tentang Sistem Ketatanegaraan dalam Islam (Khilafah): (Kajian historis dan ideologis terhadap gerakan HTI di Indonesia) - Mohammad Zainal Hamdy; Wiwik Prasetiyo Ningsih (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
History records that the government referred to by HTI is not in accordance with history, what was the form of government at the time of the Prophet and Khulafa ar-Rasidiin. In history, it is explained that the Prophet did not establish or establish a definite or absolute form of government, because the form of government is also not only a human relationship with God, but also a relationship with humans. In this case ideologically, Islam only provides a frame or limitations or can be called an indicator of goodness in government. The form of government can be adjusted according to the needs and benefit of the people.For example, the difference between the election of a caliph during the time of Abu Bakr, Umar, Usman and Ali, during the time of Abu Bakr, Abu Bakr was chosen by acclamation by representatives of the Muhajirin and Anshor from the results of deliberations and discussions. In contrast to the election of Umar to become Caliph, at that time Umar was appointed directly by Abu Bakr, also to Ustman who was appointed by the formation team for the election of the caliph and also Ali. All these differences are caused by differences and needs at that time. And these differences do not violate al-quran and as-sunnah. So it can be concluded that the echo about returning the caliphate system to the present is an inaccurate resonance, especially to the point of forbidding the existing system and infidel people who use the system, namely the democratic system.